Legal Frameworks for Higher Education in Sub-Saharan Africa - Saint, William (International Higher Education, 2010)
A shortage of research on the legal frameworks for higher education is evident in sub-Saharan Africa. In sub-Saharan Africa wide discrepancies in progress are observed. The reforms commonly promote more representative governance, quality assurance, and private provision. A few countries have enacted substantial changes to their legal frameworks. In other countries reforms have been noteworthy but less bold.